Transitional labour markets: A new European employment strategy - Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Although it has become fashionable to reject 'full employment' as a realistic objective for economic and social policy, there is one important reason to stick to this goal. 'Full employment' always reflected the idea that all persons should have the right to earn a decent living through their own work. It is this connotation of social integration by full participation in the working life that makes full employment still powerful as a regulatory idea. However, the content of this goal deserves reconsideration. The model of continuous and dependent fulltime employment is no longer up to date, although it still implicitly underlies many institutional arrangements. This 'male breadwinner norm' denies full employment participation to women on the one hand, and relieves men from full responsibility in the family life on the other hand. This paper suggests replacing this norm by the regulatory idea of transitional labour markets. – – Obwohl es Mode geworden ist, 'Vollbeschäftigung' als ein realistisches Ziel für Wirtschafts- und Sozialpolitik zu verwerfen, gibt es einen wichtigen Grund, an diesem Ziel festzuhalten. 'Vollbeschäftigung' reflektierte schon immer die Idee, daß alle Menschen das Recht haben sollten, einen menschenwürdigen Lebensunterhalt durch eigene Arbeit zu verdienen. Es ist diese Bedeutung der sozialen Integration durch volle Teilnahme am Erwerbsleben, die das Vollbeschäftigungsziel immer noch als eine wirkungsvolle regulative Idee erscheinen läßt. Dennoch bedarf ihr Inhalt einer Neubesinnung. Das Modell der kontinuierlichen und abhängigen Vollzeiterwerbstätigkeit ist längst nicht mehr zeitgemäß, obwohl es noch vielen institutionellen Arrangements als implizite Norm zugrunde liegt. Dieses 'die Männer sind die Ernährer'-Modell verweigert den Frauen einerseits die volle Beteiligung am Erwerbsleben und entlastet andererseits die Männer von jeglicher Verantwortung im Familienleben. Dieses Papier schlägt vor, diese Norm durch die regulative Idee der Übergangsarbeitsmärkte zu ersetzen.
Keywords: 330